Effect of CaO/Fe2O3 Ratio and Oil/Methanol Molar Ratio on Biodiesel Production from Waste Cooking Oil - Buchori, Luqman; Setiadi, Iqfan Dwi; Nurushofa, Faustina Alda; Anggoro, Didi Dwi (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Biodiesel is a renewable liquid fuel that can be produced through the transesterification reaction of biomass. The objective of this research was to examine the effect of comparative composition of CaO and Fe2O3 on CaO/Fe2O3 catalysts from eggshells and Fe2O3 in the production of biodiesel from waste cooking oil. In addition, it was also studied the effect of the ratio of oil and methanol on the yield and characteristics of the biodiesel produced. Catalysts were prepared through impregnation. The esterification-transesterification process was carried out with the conditions WCO:methanol molar ratio of 1:3, 1:6, 1:9, 1:12 and 1:15, catalyst (3%wt oil), heated at 65°C for 3 hours with a stirring scale of 1200 rpm. The results showed biodiesel production using CaO: Fe2O3 catalyst with the ratio of CaO: Fe2O3 70:30 and WCO:methanol molar ratio of 1:9 obtained higher yield (84.5%) compared to others. The best biodiesel yield produced is the CaO:Fe2O3 catalyst ratio of 70:30 and the WCO:methanol molar ratio of 1:9 with a biodiesel yield of 84.50% with a methyl ester content of 99.63% and a FAME yield of 84.14%. The biodiesel produced has met the requirements of the Indonesian National Standard (SNI) in terms of density and viscosity.